Bede : the Reckoning of Time - Beda Venerabilis, asi 672-735 (Translated texts for historians ;, 1988)
From the patristic age until the Gregorian calendar reform of 1582, computus – the science of time reckoning and art of calendar construction – was a subject of intense concern to medieval people. Bede’s The Reckoning of Time (De temporum ratione) was the first comprehensive treatise on this subject, and the model and reference for all subsequent teaching, discussion and criticism of the Christian calendar. The Reckoning of Time is a systematic exposition of the Julian solar calendar and the Paschal table of Dionysius Exiguus, with their related formulae for calculating dates. But it is more than a technical handbook. Bede sets calendar lore within a broad scientific framework and a coherent Christian concept of time, and incorporates themes as diverse as the theory of tides and the threat of chiliasm. This translation of the full text includes an extensive historical introduction and a chapter-by-chapter commentary. The Reckoning of Time also serves as an accessible introduction to the computus itself. This is the first full translation of this work, and beautifully edited.